Peran Kyai Ahmad Muzaini dalam Meningkatkan Kemampuan Islamic Leadership Peserta didik di SMA Takhassus As-Sahro Kepil Wonosobo - Ahmad Tafrichan; Mukromin Mukromin; Firdaus Firdaus (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Leadership is a crucial element in society, especially in the context of education. Quality leadership plays an important role in managing resources in Islamic educational institutions to achieve the vision and mission that has been set. One of the interesting aspects of leadership is Islamic Leadership, which prioritizes transcendental values as a guide in leadership. In Wonosobo, Kyai Ahmad Muzaini played an important role in shaping the character and spirit of student leadership at Takhassus As-Sahro High School. He not only teaches religious science, but also guides students in developing leadership based on Islamic teachings. This study aims to examine the role of Kyai Ahmad Muzaini in improving students' Islamic Leadership skills, as well as the impact of programs implemented in the school. With a qualitative approach, this study found that Kyai Ahmad Muzaini's success in integrating religious knowledge with practical leadership skills made a significant contribution to the development of Islamic education in Indonesia. This research is expected to provide a clear picture of the application of Islamic Leadership in Islamic education and its impact on students' character, as well as recommendations for other Islamic schools in developing leadership programs based on Islamic values.